Characteristics and application potential of municipal solid waste incineration (MSWI) bottom ashes from two waste-to-energy plants. (15th May 2015) - Tang, P.; Florea, M.V.A.; Spiesz, P.; Brouwers, H.J.H.
Highlights: MSWI bottom ashes properties related to their production time and procedure. Environmental impact evaluation of bottom ashes over time. MSWI bottom ash application potential in cement clinker production. Influence of bottom ash on cement hydration and mortar strengths. Abstract: This study focuses on municipal solid waste incineration (MSWI) bottom ash characteristics, its heterogeneity, environmental properties, and their stability in time. The physical and chemical characteristics of bottom ashes from two plants were determined over time; results show that their properties are very stable and similar to each other. As an exploratory study, bottom ash was applied in mortars without further treatment, in order to identify the limit conditions of its use as replacement material. Results show that bottom ash fines have a detrimental effect on cement hydration and strength of the mortars.